2019
DOI: 10.1038/s41467-019-09055-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids fine-tune Piezo1 mechanical response

Abstract: Mechanosensitive ion channels rely on membrane composition to transduce physical stimuli into electrical signals. The Piezo1 channel mediates mechanoelectrical transduction and regulates crucial physiological processes, including vascular architecture and remodeling, cell migration, and erythrocyte volume. The identity of the membrane components that modulate Piezo1 function remain largely unknown. Using lipid profiling analyses, we here identify dietary fatty acids that tune Piezo1 mechanical response. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
215
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(236 citation statements)
references
References 74 publications
18
215
3
Order By: Relevance
“…When cultured with DHA, PIEZO1-GFP expressing cells displayed lower activation thresholds (Fig.7B, 7C) and an increased latency of the response (Fig.7D, SI Fig.1). In contrast with a recent study employing whole-cell patch-clamping and activation of PIEZO1 by cell indentation [20], our cell-attached patch data revealed a significant sensitization to applied suction after 24 and 48 hours of PUFA enrichment ( Table 1). The activation thresholds quantified in Table 1 are in good agreement with previously published estimates [18] [43].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…When cultured with DHA, PIEZO1-GFP expressing cells displayed lower activation thresholds (Fig.7B, 7C) and an increased latency of the response (Fig.7D, SI Fig.1). In contrast with a recent study employing whole-cell patch-clamping and activation of PIEZO1 by cell indentation [20], our cell-attached patch data revealed a significant sensitization to applied suction after 24 and 48 hours of PUFA enrichment ( Table 1). The activation thresholds quantified in Table 1 are in good agreement with previously published estimates [18] [43].…”
Section: Discussioncontrasting
confidence: 99%
“…All the PIEZO1 variants studied (PIEZO1-GFP, transiently transfected WT, transiently transfected R2456H mutant and N2A native) displayed slower inactivation after cholesterol removal. These results suggest that membrane cholesterol, like other lipids [20], contributes to PIEZO1 inactivation. Cholesterol depletion increases PIEZO1-GFP diffusion in live cells.…”
Section: Electrophysiological Effects Of Membrane Cholesterol Manipulmentioning
confidence: 68%
See 2 more Smart Citations
“…Biophysical studies have shown that membrane bilayer tension changes can directly activate Piezo1 ion channels and the regulation of Piezo1's function has been attributed to the regulation of localized lipid bilayer tension changes 12,13 . This is supported by biophysical studies that Piezo1 is sensitive to specific lipid types 14 and the observations that Piezo1 is diffusively localized in plasma membranes of many cell lines with very few interaction partners identified 4,13,15,16 . However, an open question In the regulation of Piezo1 is the intimate involvement of the integrin-linked actin cytoskeleton in Piezo1's functions 17 .…”
Section: Introductionmentioning
confidence: 62%